IgE-mediated hypersensitivity to cephalosporins: Cross-reactivity and tolerability of alternative cephalosporins - Romano, Antonino; Gaeta, Francesco; Valluzzi, Rocco Luigi; Maggioletti, Michela; Zaffiro, Alessandra; Caruso, Cristiano; Quaratino, Donato (Journal of allergy and clinical immunology, 2015)
Studies regarding the cross-reactivity and tolerability of alternative cephalosporins in large samples of subjects with an IgE-mediated hypersensitivity to cephalosporins are lacking. We sought to evaluate the possibility of using alternative cephalosporins in subjects with cephalosporin allergy who especially require them. One hundred two subjects with immediate reactions to cephalosporins and positive skin test results to the responsible drugs underwent serum specific IgE assays with cefaclor and skin tests with different cephalosporins. Subjects were classified in 4 groups: group A, positive responses to 1 or more of ceftriaxone, cefuroxime, cefotaxime, cefepime, cefodizime, and ceftazidime; group B, positive responses to aminocephalosporins; group C, positive responses to cephalosporins other than those belonging to the aforementioned groups; and group D, positive responses to cephalosporins belonging to 2 different groups. Group A subjects underwent challenges with cefaclor, cefazolin, and ceftibuten; group B participants underwent challenges with cefuroxime axetil, ceftriaxone, cefazolin, and ceftibuten; and group C and D subjects underwent challenges with some of the aforementioned cephalosporins selected on the basis of their patterns of positivity. There were 73 subjects in group A, 13 in group B, 7 in group C, and 9 in group D. Challenges with alternative cephalosporins (ceftibuten in 101, cefazolin in 96, cefaclor in 82, and cefuroxime axetil and ceftriaxone in 22 subjects) were well tolerated. Cephalosporin hypersensitivity does not seem to be a class hypersensitivity. Subjects with cephalosporin allergy who especially require alternative cephalosporins might be treated with compounds that have side-chain determinants different from those of the responsible cephalosporins and have negative pretreatment skin test responses.